Faith as an option: possible futures for Christianity - Joas, Hans (Cultural memory in the present, 2014)
Introduction : secularization and intellectual honesty -- Does modernization lead to secularization? -- Does secularization lead to moral decline? -- Waves of secularization -- Modernization as culturally protestant metanarrative -- The age of contingency -- Increased options as a danger? -- Religious diversity and the pluralist society -- Religion and violence -- The future of Christianity -- Intellectual challenges for contemporary Christianity -- Conclusion : is Christianity leaving Europe behind?